2020
DOI: 10.1093/cid/ciaa072
|View full text |Cite
|
Sign up to set email alerts
|

How to Choose Target Facilities in a Region to Implement Carbapenem-resistant Enterobacteriaceae Control Measures

Abstract: Background When trying to control regional spread of antibiotic-resistant pathogens such as carbapenem-resistant Enterobacteriaceae (CRE), decision makers must choose the highest-yield facilities to target for interventions. The question is, with limited resources, how best to choose these facilities. Methods Using our Regional Healthcare Ecosystem Analyst–generated agent-based model of all Chicago metropolitan area inpatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…However, the specific facilities targeted for interventions can alter the regional value. 43 Thus, understanding patient-sharing patterns can help facilities coordinate to increase both direct and indirect benefits. Without this knowledge, a facility implementing highly successful interventions could garner benefits, but facilities that do not implement interventions may experience only limited benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the specific facilities targeted for interventions can alter the regional value. 43 Thus, understanding patient-sharing patterns can help facilities coordinate to increase both direct and indirect benefits. Without this knowledge, a facility implementing highly successful interventions could garner benefits, but facilities that do not implement interventions may experience only limited benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have reported that regional MDRO interventions (eg, registry, CHG bathing, and screening of interfacility transfers) are cost-saving. 43 , 50 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using our previously described software platform, Regional Healthcare Ecosystem Analyst (18), we generated an agent-based model of all 462 health-care facilities serving adult inpatients in the Chicago metropolitan region and the patients moving among these facilities and surrounding communities to simulate CRE spread (10,19). Web Appendix 1 provides model details as well as all model inputs (Web Table 1, available at https://academic.oup.com/ aje) and data sources; Web Figure 1 shows the flow of patients through the model.…”
Section: Regional Healthcare Ecosystem Analyst: Chicago Modelmentioning
confidence: 99%